Teacher wellbeing : Its effects on teaching practice and student learning - Turner, Kristina; Theilking, Monica (Issues in educational research, 2019)
In recent years, while there has been a considerable amount of research examining teacher wellbeing, the focus has largely been on negative states, such as burnout and stress. There are also only a limited number of studies examining the effect of positive teacher wellbeing on teaching practices and student learning. At the same time, there has been a considerable rise in the application of positive psychology strategies in professional contexts to improve wellbeing. One such strategy is the promotion of the PERMA framework, which was designed to provide a framework for human flourishing and wellbeing. The effect on teaching practice and student learning when teachers consciously use PERMA positive psychology strategies has not been examined. This research took a qualitative phenomenological approach to address a gap in current literature by exploring teachers' perspectives on the effect of consciously using positive psychology strategies on their teaching practice and student learning. Findings revealed impacts in both areas, providing support for more research into the relationship between teachers' use of positive psychology principles, teacher wellbeing, teaching practice and student learning. These findings may have applicability in other similar contexts, both nationally and internationally. [Author abstract]